Validation of a Prediction Rule for Legionella Pneumonia in Emergency Department Patients. (4th June 2019) - Bolliger, Rebekka; Neeser, Olivia; Merker, Meret; Vukajlovic, Tanja; Felder, Laetitia; Fiumefreddo, Rico; Haubitz, Sebastian; Koch, Daniel; Hammerer-Lercher, Angelika; Ottiger, Cornelia; Fux, Christoph A; Mueller, Beat; et al.
Abstract: We validated a clinical prediction rule for Legionella based on clinical parameters (dry cough, fever) and laboratory findings (C-reactive protein, lactate dehydrogenase, sodium, platelet counts) in 713 consecutive patients with community-acquired pneumonia. The Legionella Score performed well in estimating the likelihood for Legionella infection and thus may help to direct diagnostic and therapeutic decisions.